Study And Modeling Of Energy Supply At Moti Island-Ternate Based On Renewable Energy - Kahar, Bahrud; Hantoro, Ridho (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2016)
Until now in North Moluccas province especially in the district of Ternate city due to geographical conditions, electrification for the islands outside of Ternate be uneven and can not meet the overall demand for electricity. As well as Moti Island is one of the sub-districts of Ternate city, the operation of diesel generators was limited at night which hours 18:30 to 23:00 or 4.5 hours/day. The main problem is the high operating cost of diesel generator, especially of the fuel cost, availability and the high cost of spare parts. This study proposes a configuration models of hybrid power generation system on the Moti island between diesel generators and renewable energy as a solution to meet the electricity needs for 24 hours, because the Moti island has a energy of annual average solarÂ radiation is 5.96 kWh/m2/day and annual average wind speed ofÂ 3.8 m/s. Calculation and optimized for the potential of renewable energy and configurations models of hybrid power generation system using software HOMER (Hybrid Optimization Model for Renewable Energy). The simulation results provide a configuration models of the optimal hybrid power plant is the first option: PV (50%) + Diesel (50%) configuration with the NPC lowest value is US 1,531,546 and more efficient fuel consumption per year is 47.1% of the fuel consumption on the moti island for this time, And the second option is an alternative configuration: PV (70%) + Diesel (30%) configuration with a NPC value is US 1,577,512 and also more has efficient fuel consumption per year 64.3%.